MODEL STRATEGI PENINGKATAN DAYA SAING PRODUK BERBASIS EKONOMI KERAKYATAN DAN PANCASILA PADA UMKM TEH KELOR - Karim, Kasnaeny; Yunus, Sattar; Tajibu, Muhammad Jibril (Bisma: Jurnal Bisnis dan Manajemen, 2023)
The People's economics at this time needs to be developed to increase community participation in the economic sector. For this reason, guidance is needed that comes from the state philosophy, namely Pancasila. The study aims to determine how to increase product competitiveness based on people's economics and Pancasila in Moringa Tea MSMEs in Makassar. The SWOT analysis method is used to formulate a strategy model for increasing product competitiveness by first identifying factors that can increase competitiveness by analyzing strengths and weaknesses. The research results show that the strategy model that can be implemented to increase the competitiveness of Moringa Tea MSME products based on people's economics and Pancasila is the SO model, namely the combination of strengths and opportunities through (1) Strengthening product distribution, (2) Implementing digital/online marketing, (3) Collaborating with parties who play a role in product development and marketing, (4) Implementing promotions conventionally or based on Information Technology, (5)Expanding innovations in packaging, (6) Innovating products that have more added value, (7) Improving MSME human resource capabilities, (8) Completing other permits and certifications, and (9) Improving the taste of Moringa tea.